The Humanistic-Anthropocosmic Paradigm as a Framework for Transforming Slum Settlements in Indonesia - Purbadi, Yohanes Djarot; Lake, Reginaldo Christophori (University of Merdeka Malang, 2024)
The aim of this paper is to elucidate the new humanistic-anthropocosmic paradigm as a framework for transforming urban slum settlements in Indonesia amidst climate change and within a multidimensional living context. The paper elaborates on the ideas of Father Mangunwijaya and draws inspiration from the encyclical Laudato Si. The methodology employed involves a literature review and reflection on the paradigm of transforming slum settlements that have been implemented in several cities in Indonesia. Findings suggest that the Humanistic-Anthropocosmic paradigm, a fusion of Father Mangunwijaya's ideas and inspiration from the encyclical Laudato Si, holds the potential to facilitate sustainable and environmentally friendly transformation of urban slum settlements, considering social, economic, and environmental aspects. This article contributes to the development of a paradigm for transforming urban slum settlements rooted in humanistic architecture, education for liberation, ecological spirituality, integral ecology, and anthropocosmism.